Twelve toll-like receptor (TLR) genes in the family Equidae - comparative genomics, selection and evolution - Stejskalova, K; Janova, E; Splichalova, P; Futas, J; Oppelt, J; Vodicka, R; Horin, P (Veterinary research communications, 2024)
Toll-like receptors (TLRs) represent an important part of the innate immune system. While human and murine TLRs have been intensively studied, little is known about TLRs in non-model species. The order Perissodactyla comprises a variety of free-living and domesticated species exposed to different pathogens in different habitats and is therefore suitable for analyzing the diversity and evolution of immunity-related genes. We analyzed TLR genes in the order Perissodactyla with a focus on the family Equidae. Twelve TLRs were identified by bioinformatic analyses of online genomic resources; their sequences were confirmed in equids by genomic DNA re-sequencing of a panel of nine species. The expression of TLR11 and TLR12 was confirmed in the domestic horse by cDNA sequencing. Phylogenetic reconstruction of the TLR gene family in Perissodactyla identified six sub-families. TLR4 clustered together with TLR5; the TLR1-6-10 subfamily showed a high degree of sequence identity. The average estimated evolutionary divergence of all twelve TLRs studied was 0.3% among the Equidae; the most divergent CDS were those of Equus caballus and Equus hemionus kulan (1.34%) in the TLR3, and Equus africanus somaliensis and Equus quagga antiquorum (2.1%) in the TLR1 protein. In each TLR gene, there were haplotypes shared between equid species, most extensively in TLR3 and TLR9 CDS, and TLR6 amino acid sequence. All twelve TLR genes were under strong negative overall selection. Signatures of diversifying selection in specific codon sites were detected in all TLRs except TLR8. Differences in the selection patterns between virus-sensing and non-viral TLRs were observed.
Keywords: toll-like receptor 3; Toll-Like Receptor 1; Toll-Like Receptor 3; genomika; Perissodactyla; Toll-Like Receptors; Equidae; Transpecies haplotype sharing; Mice; Odd-toe ungulates; Horses; toll-like receptory; zvířata; Humans; Genomics; Innate immunity; koně; fylogeneze; toll-like receptor 1; myši; Equid; Phylogeny; lidé; Toll-like receptor; Animals